Using Structured Instruments in Managing a Portfolio of Financial Assets from the Standpoint of Protecting Capital and Increasing Profits - BONDARENKO, Tatiana Grigorievna; DMITRIEV, Nikolai Valentinovich; ISAEVA, Ekaterina Anatolievna; AYYUBOV, Veysal Seyfal (Journal of Advanced Research in Law and Economics; Vol 9 No 2 (2018): JARLE Volume IX Issue 2(32) Spring 2018, 2018)
The article analyzes practical approaches to managing a portfolio of financial assets through operations with financial vehicles that allow implementing strategies with a guarantee of preserving the capital value. Development of the theory of financial assets portfolio formation in historical retrospect is analyzed, and ways of portfolio formation using scientific theories of such economists as Harry Markowitz and William Sharpe are reviewed. Classification of investment portfolios is provided, and structured instruments allowing simultaneously minimizing the risk of capital loss and increasing the potential yield of financial assets portfolio are offered on their basis. The developed recommendations on improving the management of the financial assets portfolio using structured instruments based on the conducted analysis allowed to select and adapt several real market structured instruments that made it possible both to implement the function of capital protection and form the portfolio yield at the same time.